Turn Of The Short Story Malim Pesong Into Drama Manuscript As Teaching Material - Muhammad Tommy Lumban Tobing; Teguh Trianton; Dian Syahfitri (Universitas Negeri Semarang, 2025)
Adapting the short story Malim Pesong is considered as a process to create new activities that can then be used as a reference for new creative processes in learning while introducing local writers to students. The purpose of this study focuses on the creative process of creating the adaptation of the short story Malim Pesong into a drama script and to explain the process of adapting the Malim Pesong drama script into teaching materials in drama texts for grade 8 junior high school. This study uses a qualitative research method with a qualitative descriptive approach. The results of this study found that there were several processes of adaptation from short stories to drama scripts so that they could be used as teaching materials, going through stages such as: 1) Understanding the intrinsic elements of short stories; 2) Classifying parts of short stories into scenes; 3) Writing drama scripts; 4) Classifying changes that occur in the adaptation process; and 5) The process of adjusting the results of the adaptation as teaching materials. The findings in this study indicate that the phenomenon of adapting a literary work into a drama script is very good if it is carried out massively in the learning process. Adapting a work as teaching material is important to increase students' knowledge in the process of creating drama scripts. This creation can have an impact on increasing knowledge and become a new way for the community to develop drama scripts with new stories through short stories chosen by the community.